A Pilot Study on the Age-Dependent, Biomechanical Properties of Longitudinal Ligaments in the Human Cervical Spine - Narendra Singh; Ana Trajkovski; Jovan Trajkovski; Robert Kunc; Jose Felix Rodriguez Matas (Bioengineering)
The cervical spine ligaments, including the anterior longitudinal ligament (ALL) and posterior longitudinal ligament (PLL), play a key role in maintaining spinal stability by limiting excessive movements. This study investigates how ageing affects the mechanical properties of these ligaments. We analysed 33 samples from 12 human cervical spines (15 ALL, 18 PLL), averaging data from the same donors for independent analysis, resulting in 18 final samples (8 ALL, 10 PLL). To explore age-related changes, we classified the samples into two groups—below and above 50 years old—aligning with the peak incidence of major musculoskeletal disorders. The investigation concentrated on the effects of age on four mechanical parameters of the uniaxial stress–stretch curve: initial tangent stiffness (<semantics>E0</semantics>), maximum tangent stiffness (<semantics>Em</semantics>), ultimate stress (<semantics>Pu</semantics>) and ultimate stretch (<semantics>λu</semantics>). When the age effect is neglected, then the behaviours of both the ALL and PLL appeared similar. However, when introducing age as a variable into the context of the ALL and PLL, statistically significant differences became evident. The findings underscored a reduction in maximum tangent stiffness (p-value = 0.0147), ultimate stress (p-value = 0.0009), and ultimate stretch (p-value = 0.0024) when the ALL and PLL were grouped under and above 50 years as a consequence of ageing.